PENINGKATAN HASIL BELAJAR MATERI PEMBIASAN CAHAYA MELALUI STRATEGI TEAM PAIR SOLO DALAM PEMBELAJARAN KOOPERATIF - Alya Imelda; Tutut Nurita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the improvement of students’ learning outcomes through the implementation of the Team Pair Solo strategy in cooperative learning on light refraction material. This research used a pre-experimental design with a one group pretest-posttest design. The subjects were 28 eighth-grade students of SMP Negeri in Surabaya. Data were collected through tests, observations, and questionnaires. The results showed that the data were normally distributed based on the Shapiro-Wilk test. The N-Gain analysis showed an increase in students’ learning outcomes in the medium to high category. In addition, the implementation of learning was categorized as very good, and students gave positive responses to the learning process. Therefore, the Team Pair Solo strategy effectively improves students’ learning outcomes.